Implementasi Kebijakan Pemberdayaan Usaha Mikro dalam Perspektif Hukum: Peran Dinas Koperasi dan UMKM pada Masyarakat Pesisir Karangantu - Ahmad Lanang Citrawan; H. E. Rakhmat Jazuli (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of the Department of Cooperatives, Micro, Small and Medium Enterprises, Industry and Trade of Serang City in implementing the empowerment and development of micro-enterprises in the coastal community of Karangantu based on Regional Regulation Number 3 of 2015. Employing an empirical juridical approach with a descriptive-analytical specification, this research analyzes the interaction between legal norms and their practical implementation through primary and secondary data. The findings reveal that although the regulatory framework, including Law Number 20 of 2008 and relevant local regulations, provides a comprehensive legal basis, its implementation remains suboptimal due to structural, administrative, and socio-economic constraints. Key challenges include weak institutional coordination, inadequate performance-based monitoring systems, limited access to financing and digital markets, and low community participation. These conditions indicate a significant gap between normative expectations and empirical realities. The study concludes that strengthening institutional capacity, improving participatory governance, and integrating adaptive policy mechanisms are essential to enhance the effectiveness and sustainability of micro-enterprise empowerment in coastal areas.